2015
DOI: 10.3390/molecules20045468
|View full text |Cite
|
Sign up to set email alerts
|

Stevia Rebaudiana Bert. Leaf Extracts as a Multifunctional Source of Natural Antioxidants

Abstract: The aim of the presented study was to characterize the content and biological activity of extracts prepared from dried Stevia rebaudiana leaves with potential application in the food or cosmetic industry. Aqueous (A), ethanolic (E) and glycol-aqueous (GA) extracts were analyzed for the content of polyphenols and proteins, showing that the highest amount of phenols (15.50 mg/g) and flavonoids (3.85 mg/g) contained GA. All extracts contained significant amount of protein (69.40–374.67 mg/g). Between analyzed ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 57 publications
9
70
0
2
Order By: Relevance
“…Shukla et al 2009 found 61.5 mg/g GAE from the ethanol extract of Stevia leaves through Soxhlet. Gawel-Beben et al 2015 found similar values of phenolic compounds in ethanol extract of dried leaves from Stevia rabaudiana. The values found in the present study indicate that these compounds should be further evaluated for their antioxidant potential in food and drinks, and further demonstrates that the ethyl acetate fraction has the greatest potential for will provide additional benefits in terms of oxidative.…”
Section: Total Phenolic Compoundssupporting
confidence: 49%
See 2 more Smart Citations
“…Shukla et al 2009 found 61.5 mg/g GAE from the ethanol extract of Stevia leaves through Soxhlet. Gawel-Beben et al 2015 found similar values of phenolic compounds in ethanol extract of dried leaves from Stevia rabaudiana. The values found in the present study indicate that these compounds should be further evaluated for their antioxidant potential in food and drinks, and further demonstrates that the ethyl acetate fraction has the greatest potential for will provide additional benefits in terms of oxidative.…”
Section: Total Phenolic Compoundssupporting
confidence: 49%
“…Stevia UEM-13 therefore presented a ratio RebA/Stev much higher (2.27) than the wild varieties that have inferiors values to 1 (Kovylyaeva et al 2007, Gardana et al 2010, Gupta et al 2013, Madan et al 2010. The new cultivar has significant levels of bioactive compounds when compared with other wild varieties (Gawel-Beben et al 2015, Pasquel et al 2000, Wölwer-Rieck 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the growing trend in the use of plant extracts in the food and beverage industry, the use of stevia from Stevia rebaudiana Bertoni plays a significant role (Gaweł‐Bȩben et al . ). Stevia is a natural sweetener whose commercial importance is linked to the purified steviol glycosides extracted from the plant's leaves, which are noncaloric molecules that have a high sweetening potential (Giri et al .…”
Section: Introductionmentioning
confidence: 97%
“…The therapeutic effects associated with consumption of stevia leaves and their crude extracts include antimicrobial, antihypertensive, antihyperglycaemic and immunoregulatory effects, all of which have been linked to the bioactive phytoconstituents of stevia leaves (Wölwer‐Rieck ; Gaweł‐Bȩben et al . ).…”
Section: Introductionmentioning
confidence: 97%